Determination of α1-acid glycoprotein (AGP) concentration by HPLC in patients following local infiltration analgesia for primary total hip arthroplasty and its relation to ropivacaine (total and unbound) - Abbas, Muhammad; Alossaimi, Manal A.; Altamimi, Abdulmalik S. A.; Alajaji, Mai; Watson, David G.; Shah, Sayyed I.; Shah, Yasar; Anwar, Mohammad S. (Frontiers in Pharmacology, 2023)
Introduction: This study was performed to determine the levels of α1-acid glycoprotein (AGP) in old-age patients undergoing total hip arthroplasty. AGP is considered an acute phase protein produced during the acute phase reaction in the body to various stimuli; their proper monitoring is thus important. Methods: In order to study how AGP concentrations in old age patients change in response to surgical stress (total hip arthroplasty), a high-performance liquid chromatography assay was performed to measure AGP levels. AGP was isolated from the plasma by adding perchloric acid and was analyzed using PLRP-S 4000°A column. The mobile phase consisted of 1 mL TFA/L of water (Solvent A pH 2) and 1 mL TFA/L of acetonitrile (Solvent B). The gradient used was as follows: 0 min 18% B and 82% A, 15 min 60% B and 40% A, and 17 min 60% B and 40% A followed by column re-equilibration for 7 min before the next injection. AGP peak was obtained between 8.8 and 8.9 min. The method was fully optimised according to established guidelines. Results: The data obtained were analyzed on ChromQuest software. AGP concentrations were determined in all samples, including baseline and samples taken at different timed intervals. The peak for AGP was obtained between 8.8 and 8.9 min for both standard AGP and patient plasma. The graphs indicate that AGP concentration in almost all patient samples increased considerably, especially after 4 h and 24 h—for example, initial concentration in patient 1 was 10.36 mg/100 mL but, after 24 h, increased to 23.50 mg/100 mL. There was thus almost a 13 mg/100 mL increase in 24 h, which is confirmed by AGP concentration increasing after various conditions, including surgery. The increased plasma protein binding was comparatively associated with the unchanged free fraction of the drug. Conclusion: This surgically induced increase in AGP concentration resulted in increased plasma protein binding of the drug (ropivacaine), which in turn kept the free portion of ropivacaine stable during the postoperative period.